Economic Empowerment of Coastal Communities Through Sustainable Marine Ecotourism Management in Gili Balu, West Sumbawa Regency - Jalaluddin; Lidia Wati (Yayasan Siti Widhatul Faeha, 2025)
Gili Balu in West Sumbawa Regency has significant potential for developing sustainable marine ecotourism that can drive the economic empowerment of coastal communities. This study aims to develop an economic empowerment model based on ecotourism management with active community involvement. A case study method with a qualitative approach was employed through in-depth interviews, direct observations, and analysis of policy documents. The findings reveal that community participation in ecotourism management enhances awareness of natural resource conservation and provides economic benefits. However, challenges remain, including low entrepreneurial capacity, inadequate infrastructure, and social exclusion in tourism area management. The main recommendations are the establishment of the Merah Putih Cooperative as a platform for community participation, improvement of education and training programs, as well as strengthening digital promotion and infrastructure development. The study concludes that integrating environmental conservation with the enhancement of local economic capacity is key to sustaining ecotourism in Gili Balu. These findings imply the need for policies that support collaborative, community-based, and locally adaptive management to preserve ecosystems while improving the livelihoods of coastal communities.